Assessing the efficacy and tolerability of PET-guided BrECADD versus eBEACOPP in advanced-stage, classical Hodgkin lymphoma (HD21): a randomised, multicentre, parallel, open-label, phase 3 trial - Borchmann, Peter; Ferdinandus, Justin; Schneider, Gundolf; Moccia, Alden; Greil, Richard; Hertzberg, Mark; Schaub, Valdete; Hüttmann, Andreas; Keil, Felix; Dierlamm, Judith; Hänel, Mathias; Novak, Urban; et al. (The lancet, 2024)
Background - Intensified systemic chemotherapy has the highest primary cure rate for advanced-stage, classical Hodgkin lymphoma but this comes with a cost of severe and potentially life long, persisting toxicities. With the new regimen of brentuximab vedotin, etoposide, cyclophosphamide, doxorubicin, dacarbazine, and dexamethasone (BrECADD), we aimed to improve the risk-to-benefit ratio of treatment of advanced-stage, classical Hodgkin lymphoma guided by PET after two cycles. - Methods - This randomised, multicentre, parallel, open-label, phase 3 trial was done in 233 trial sites across nine countries. Eligible patients were adults (aged ≤60 years) with newly diagnosed, advanced-stage, classical Hodgkin lymphoma (ie, Ann Arbor stage III/IV, stage II with B symptoms, and either one or both risk factors of large mediastinal mass and extranodal lesions). Patients were randomly assigned (1:1) to four or six cycles (21-day intervals) of escalated doses of etoposide (200 mg/m2 intravenously on days 1-3), doxorubicin (35 mg/m2 intravenously on day 1), and cyclophosphamide (1250 mg/m2 intravenously on day 1), and standard doses of bleomycin (10 mg/m2 intravenously on day 8), vincristine (1·4 mg/m2 intravenously on day 8), procarbazine (100 mg/m2 orally on days 1-7), and prednisone (40 mg/m2 orally on days 1-14; eBEACOPP) or BrECADD, guided by PET after two cycles. Patients and investigators were not masked to treatment assignment. Hierarchical coprimary objectives were to show (1) improved tolerability defined by treatment-related morbidity and (2) non-inferior efficacy defined by progression-free survival with an absolute non-inferiority margin of 6 percentage points of BrECADD compared with eBEACOPP. An additional test of superiority of progression-free survival was to be done if non-inferiority had been established. Analyses were done by intention to treat; the treatment-related morbidity assessment required documentation of at least one chemotherapy cycle. This trial was registered at ClinicalTrials.gov (NCT02661503). - Findings - Between July 22, 2016, and Aug 27, 2020, 1500 patients were enrolled, of whom 749 were randomly assigned to BrECADD and 751 to eBEACOPP. 1482 patients were included in the intention-to-treat analysis. The median age of patients was 31 years (IQR 24-42). 838 (56%) of 1482 patients were male and 644 (44%) were female. Most patients were White (1352 [91%] of 1482). Treatment-related morbidity was significantly lower with BrECADD (312 [42%] of 738 patients) than with eBEACOPP (430 [59%] of 732 patients; relative risk 0·72 [95% CI 0·65-0·80]; p<0·0001). At a median follow-up of 48 months, BrECADD improved progression-free survival with a hazard ratio of 0·66 (0·45-0·97; p=0·035); 4-year progression-free survival estimates were 94·3% (95% CI 92·6-96·1) for BrECADD and 90·9% (88·7-93·1) for eBEACOPP. 4-year overall survival rates were 98·6% (97·7-99·5) and 98·2% (97·2-99·3), respectively. - Interpretation - BrECADD guided by PET after two cycles is better tolerated and more effective than eBEACOPP in first-line treatment of adult patients with advanced-stage, classical Hodgkin lymphoma. - Funding - Takeda Oncology.